Construction and Import of Ethnic Categorisations: Allochthones in The Netherlands and Belgium - Dirk Jacobs; Andrea Rea (Fondazione Eni Enrico Mattei (FEEM), 2006)
Schematically one can distinguish two traditions related to ethnic statistics in Europe. In France, Germany and most southern European countries, the dominant statistical categorisations merely distinguish individuals on the basis of their nationality. In contrast, most northern European countries have been producing data on the ethnic and/or foreign origin of their populations. Belgium is caught somewhere in between these two traditions. The French speaking part of Belgium tends to follow the French tradition of refusing ethnic categorisation, while the Flemish (the Dutch speaking part) try to copy the Dutch model in distinguishing allochthones and autochthones. This contribution wants to offer an analysis of the construction of ethnic categories as it has been undertaken in the Dutch context. It equally wants to shed light on how the category of allochthones has been (partially) imported into the Belgian context and what the consequences are.
Keywords: B40; 330; Ethnic Categorisation; Statistics; Allochthones; the Netherlands; Belgium